Peramalan Jumlah Wisatawan Kabupaten Belitung Menggunakan Simulasi Monte Carlo - Marcelina, Elen; Agustin, Tria; Luthfiyaturrohmah, Khilma; Octaviani, Julia; Pramita, Agnes; Monika, Ines; Dalimunthe, Desy Yuliana; Nasrun, Aja (Universitas Negeri Gorontalo, 2024)
One of Indonesia's mainstay sectors in receiving foreign exchange is tourism, especially during the Covid-19 pandemic, tourism contributed $34 billion to state revenue. The tourism sector needs to be developed to support the country's economic growth. One of the priority destinations in Indonesia that can be developed is Bangka Belitung. The purpose of this study is to forecast the number of tourists in Belitung Regency so that it can facilitate the provision of facilities that support the tourism sector as well as promotional strategies to introduce tourist attractions in Belitung Regency to the general public. This study used data on the number of tourists in 2021, 2022, and 2023 in Belitung Regency which was analyzed using the Monte Carlo method. The accuracy of forecasting results is measured based on the Mean Absolute Percentage Error (MAPE) value. The number of tourists from this forecast is in accordance with the pattern of actual tourist data in Belitung Regency.The MAPE value in forecasting the number of tourists in Belitung Regency in 2022 is 21.45%, which means that the prediction results produced are said to be good, while in 2023 it has an accuracy rate of 7.56%, which means that the prediction results are said to be very good.